Is Higher Education Internationalizing In Turkey? - Findik, Leyla Yilmaz (European Scientific Journal, ESJ, 2016)
European countries has undergone many reforms and strategies based on Bologna Process objectives to become key players in this global knowledge network. This internationalization phenomenon has affected various aspects of Turkish higher education system and Turkey set an agenda to benefit from this international environment and attract foreign students. The main aim of the study is to discuss internationalization in higher education and review of the present status of student mobility in higher education in Turkey after the launch of Bologna Process. The study will provide a picture of internationalizing and mobility in higher education in Turkey to address strategic questions related to the future of higher education in Turkey, and to discuss in detail with the aim of shedding light on new planning. The research was structured as a descriptive study and used secondary data received from Council of Higher Education (CoHE) published on the web site as well as international documents and reports. According to the findings of the study, it is impossible at that moment to report accurately that much progress has been made on internationalizing in higher education in Turkey.